PELUANG HOME GARDENING SELAMA PANDEMI COVID-19 DI MEDAN SEKITAR - Juliana Br. Simbolon; Roida Ervina Sinaga; Jupianus Sitepu (Universitas Quality, 2021)
The aim of this study is to identify the benefits and opportunities of home gardening during the covid-19 pandemic. The methods of this research is used descriptive qualitative in which it intends to encrypt and interpreta data condition obtained through observation, interview. The aim of this research is to know the benefits and opportunities of the home gardening to communities in surrounding terrain during the pandemic. Tehe benefits of planting the decorated plant the academic environment a wide variety of plant colors is also dim use as a business opportunity in view of the current unstable economy. Various crops were planted, and the most attention stolen was the houseplant that came back the boom. Different kinds flowers planted in garden such as aglonem, anthurium, begonia, talas, etc.